The impact of service marketing mix and customer satisfaction on savings decisions at Bank Sinarmas, Garut branch - Garliani, Gita; Setiawan, Rahyuniati (Fakultas Ekonomi Universitas Garut, 2024)
This research was conducted at bank sinarmas branch in garut. The purpose of this study is to determine how the service marketing mix, customer satisfaction, and savings decisions are at bank sinarmas branch in garut, and to what extent the influence of the service marketing mix on savings decisions at bank sinarmas branch in garut, as well as the extent of the influence of customer satisfaction on savings decisions at bank sinarmas branch in garut. This research adopts a quantitative approach, utilizing data collected in numerical form that will be tested using statistical methods. The data collection techniques employed in this study include questionnaires and literature reviews. The population in this research consists of savings account holders at bank sinarmas branch in garut, totaling 100 individuals determined using the lemeshow formula. To obtain data, the author distributed questionnaires to customers comprising 30 questions, consisting of 18 questions related to the service marketing mix, 7 questions about savings decisions, and 5 questions regarding customer satisfaction. Hypothesis testing was conducted using statistical data analysis with a path analysis model. Based on the research findings, it can be concluded that the service marketing mix significantly influences savings decisions and customer satisfaction.Key words: services marketing mix, customer satisfaction, saving decisions